VD_FINDINFO HC / 2023 / 761 vom 16. November 2023 - VD Tribunal cantonal (2023)
RETRAITVOIE DE DROIT, FRAIS JUDICIAIRES, ASSISTANCE JUDICIAIRE | 122 al. 1 let. a CPC (CH), 65 al. 2 TFJC (2010), 67 al. 2 TFJC (2010)